PEMODELAN SISTEM E-RECRUITMENT KARYAWAN BARU BERBASIS WEB STUDI KASUS PT.XYZ - Mashudi, Mashudi (POLITEKNIK LP3I JAKARTA, 2014)
Recruitment of employees within an organization is important because it has a function to gather the human resources in an organization, the growing technological advances have been demanding the company to apply the name of e-recruitment is the recruitment system that utilizes the Internet. There are some differences in this system than if the company applying traditional recruitment system, but the difference is not a problem because the company can obtain many benefits from this online system, the cost savings, ease of use for the candidate, the ease of use for the organization, increasing the speed of the recruitment process and success in finding a potential job candidates. Although the application of the company no one has been successful, but some large companies such as MICROSOFT or ORACLE has implemented an e-recruitment system. Keyword : E- Recruitment, online, web